Retaining wall construction (gabion wall) / Muhamad Nukman Nadir Zolkapli - Zolkapli, Muhamad Nukman Nadir (Universiti Teknologi MARA, Perak, 2022)
Walls are one of the most important structure elements of a building. A wall plays several functions in the performance of a house and these functions need to be fully understood in order to create suitable and comfortable building as well as providing privacy also as protection from weather. This report will discuss about gabion wall work for the retaining wall of the building. This report was conducted for The Construction is Projek Menggantikan Jambatan Baru RC B149/000/80 Melintasi Sungai Kundang Di Jalan Kundang B149, Daerah Gombak , Selangor Darul Ehsan. The objective of this report is to analyze the construction of retaining wall and the way how it carried out. It will focus on the whole process of retaining wall (gabion wall) construction. It also investigate the equipment and machinery in the methods of gabion wall construction and to determine the time that have been used for the construction. This report will also look to at the advantages and disadvantages in wall construction that would fulfil the criteria of gabion wall.